Problematika Dakwah di Era Globalisasi - Setiana, Wiryo (UIN Sunan Gunung Djati Bandung, 2009)
The challenge and dawah problems getting time getting weight. At global era development and changes in society as happening more meteoric. Communications technology development have given herculean deep influence in all life aspect, particularly affecting capital owners, world power, exploited globalization as media for hegemony to culturize, driving in influence and changes thinks pattern society universalizes. What do will happen by living moslem society if function of dawah control is not implemented.Keywords:Dakwah, Tantangan Dakwah, Problematika Dakwah, Era Globalisasi,dan Kontekstualisasi Dakwah